The development of national crafts in the southern regions of Uzbekistan - Mamarajabov, Gayrat (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
This article reflects the development of handicrafts in the southern regions of the Republic of Uzbekistan, the types of handicraftsspecific to this region, the national values formed in the oasis and continuing to this day. The article also reflects the conditions created by the state for artisans during the years of independence and the issue of state policy